Histaminergic regulation of food intake - Khouma, Axelle; Moeini, Moein Minbashi; Plamondon, Julie; Richard, Denis; Caron, Alexandre; Michael, Natalie Jane (Frontiers in Endocrinology, 2023)
Histamine is a biogenic amine that acts as a neuromodulator within the brain. In the hypothalamus, histaminergic signaling contributes to the regulation of numerous physiological and homeostatic processes, including the regulation of energy balance. Histaminergic neurons project extensively throughout the hypothalamus and two histamine receptors (H1R, H3R) are strongly expressed in key hypothalamic nuclei known to regulate energy homeostasis, including the paraventricular (PVH), ventromedial (VMH), dorsomedial (DMH), and arcuate (ARC) nuclei. The activation of different histamine receptors is associated with differential effects on neuronal activity, mediated by their different G protein-coupling. Consequently, activation of H1R has opposing effects on food intake to that of H3R: H1R activation suppresses food intake, while H3R activation mediates an orexigenic response. The central histaminergic system has been implicated in atypical antipsychotic-induced weight gain and has been proposed as a potential therapeutic target for the treatment of obesity. It has also been demonstrated to interact with other major regulators of energy homeostasis, including the central melanocortin system and the adipose-derived hormone leptin. However, the exact mechanisms by which the histaminergic system contributes to the modification of these satiety signals remain underexplored. The present review focuses on recent advances in our understanding of the central histaminergic system’s role in regulating feeding and highlights unanswered questions remaining in our knowledge of the functionality of this system.